1991
DOI: 10.1093/infdis/164.5.954
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Cytopathic Small Round Viruses with BS-C-l Cells from Patients with Gastroenteritis

Abstract: Fecal extracts from 12 subjects in outbreaks of oyster-associated nonbacterial gastroenteritis were inoculated with BS-C-1 cells for isolation of the causative viruses. Cytopathic agents were isolated from 3 patients. No cross-neutralizing reactions were observed between the isolates and prototypes of human enteroviruses. The isolates were approximately 30 nm in diameter and had a distinct ultrastructure resembling that of astroviruses. Four polypeptide bands with molecular sizes of 42, 28, 27, and 22 kDa were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
196
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(200 citation statements)
references
References 10 publications
2
196
1
1
Order By: Relevance
“…Aichi virus, which is associated with human acute gastroenteritis (41), is a member of the genus Kobuvirus of the family Picornaviridae (31,42). This virus was first isolated in 1989 from a stool specimen from a patient with oyster-associated nonbacterial gastroenteritis in Aichi, Japan (41), and the complete genome sequence was determined in 1998 (42).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aichi virus, which is associated with human acute gastroenteritis (41), is a member of the genus Kobuvirus of the family Picornaviridae (31,42). This virus was first isolated in 1989 from a stool specimen from a patient with oyster-associated nonbacterial gastroenteritis in Aichi, Japan (41), and the complete genome sequence was determined in 1998 (42).…”
mentioning
confidence: 99%
“…This virus was first isolated in 1989 from a stool specimen from a patient with oyster-associated nonbacterial gastroenteritis in Aichi, Japan (41), and the complete genome sequence was determined in 1998 (42). The single-stranded, positive-sense RNA genome of Aichi virus consists of 8,280 nucleotides (nt) and a poly(A) tract and encodes a polyprotein of 2,432 amino acids (aa) (34,42).…”
mentioning
confidence: 99%
“…A standard Aichi virus strain, A846/88, was grown in Vero cells. The virion was purified by CsCl centrifugation as described previously (42). RNA was extracted by proteinase K treatment, followed by phenol-chloroform extraction and ethanol precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…Aichi virus was first isolated in 1989 from a stool specimen from a patient with oyster-associated nonbacterial gastroenteritis in Aichi, Japan (42). The complete genome sequence of this virus was determined, and the genome organization revealed that this virus is a member of the family Picornaviridae (45).…”
mentioning
confidence: 99%
“…Sapovirus, another genus of the family Caliciviridae, HAstV (41), and enteric type 40 and 41 HAdVs have also been associated with diarrhea. Aichi virus (42) has recently been classified into the Kobuvirus genus in the Picornaviridae family and has been associated with oyster consumption.…”
mentioning
confidence: 99%